Formaldehyde-free wood adhesives based on protein materials from various plant species - Bernardo Grossi; Benedetto Pizzo; Francesco Siano; Antonio Varriale; Rosanna Mabilia (Results in Engineering)
This study investigated the use of different protein materials to produce formaldehyde-free wood adhesives for plywood production. Biomass from various sources offers a steady supply of raw materials that could encourage wider use. The aim of the study was therefore to find proteins that are naturally high performing without needing costly pre-treatment (e.g., purification or physical processes), in order to reduce costs. Materials from seven plants (soybean, cotton, hemp, carob, grape, maize, and jatropha) were analysed for water resistance and mechanical strength in dry and wet conditions using wood-wood joints (WWJ) and the tests used to characterise plywood. The proteins were tested alone and with polyamide-amine epichlorohydrin (PAE), and blends of different proteins were also evaluated.The results showed that drying conditions affected the insoluble fraction (InFr) and shear strength in WWJ, with variations related to protein content and carbohydrate composition. Protein-rich materials (e.g., soybean isolate) generally exhibited higher dry shear strengths (>10 N/mm²) compared to materials with lower protein content (<7 N/mm²). Wet strengths were generally low or even absent for flours and concentrates. Jatropha concentrate was a notable exception, achieving D3 adhesive classification even without additives. PAE treatment significantly increased wet shear strengths, often exceeding 2 MPa (the minimum for D3 adhesives). Flours and concentrates (except soybean flour) showed the highest strengths (≥3 MPa). PAE probably interacted with both proteins and carbohydrates to improve performance. Moreover, the study showed that protein materials can be blended to enhance adhesive strength, potentially reaching the levels of the best-performing formulations.